Vyvařované půdy tundry Krkonoš a Abisko Mts - předběžná srovnávací studie - Lukešová, A. (Alena); Kociánová, M.; Váňa, J.; Štursová, H.; Elster, J. (Josef); Harčarik, J.; Halda, J.; Kocourková, J.; Jankovská, V. (Vlasta) (2010)
Frost boil soils represent an individual patterned grounds tundra-ecosystem, affected by permafrost. Our comparative study between Abisko Mts and the Giant Mts confirm "boiling" also in the Giant Mts, i.e. out of permafrost zone. Expulsion of molisol towards the soil surface is more affected by hydrodynamic processes than by freezing ones. "Boiling process" was, contrary to the Abisko Mts, where it represents an ordinary phenomenon, detected on a very cramped area (in order of cm.sup.2./sup.), entirely in the central parts of several fossil sorted polygons, nonsorted circles and in soil scars. Our study is the first ever published evaluation of living organisms colonizing frost-boiled soils both in Abisko and the Giant Mts. Species composition of organisms, algal biomass and basic soil physical and chemical parameters were analyzed at 4 localities in Abisko area and at 3 localities in the Giant Mts.